Can a Monkey play a Bitch? Hanumant and Sarama - Ježić, Mislav (2005)
Already Hermann Jacobi (1893) distinguished the second part of the Rama narrative in books 3 to 7 from book 2, which he saw as a historical saga. He interpreted the second part as based on myths, and singled out the myth of Sarama and the Panis as particulary corresponding to the story about Hanumant finding Sita on the island of the Raksasas. This paper tackles that question once more, and tries to sharpen the comparative tools according to the progress of the Indo-European methodology since Jacobi's time, especially the methodology of reconstruction of poetic formulae, and of the folk tale theory, particulary the fairy tale morphology as described by Vladimir Propp. The results of that comparative scrunity confirm Jacobi's insights and endorse the identification of the Vedic Vala myth as the model for the second part of the Rama narrative, but lead to a different interpretation of the character of Sita, and of Hanumant and Sarama, as well as of the meaning of the myth, by discovering a different semiotic framework for it. They also raise the question of the common structure of fairy tales in a different context. In this way this article may open a deeper perspective for the philological, structural and historical, understanding of the relationship between hieratic mythic poetry, epic poetry and fairy tales as literary genres.
Projekt MZOS
ENG